Impact of Active Cooling Systems on Solar Panel Efficiency and Net Energy Production - Ferry R. A ., Bukit; Yanuar Zulardiansyah, Arief; Arman, Sani; Riswan, Dinzi; Pribadi Prima, Sitompul (IEEE, 2026)
The operation of solar panels is highly dependent on environmental conditions to provide a reliable power source. Temperature is one of the important ecological factors that directly affect the performance of solar panels, as higher operating temperatures reduce efficiency. In this study, two active cooling systems were applied to solar panels: water and air cooling using a heatsink and fan. The aim was to analyze the efficiency by comparing the energy produced by the panels with the energy consumed by the cooling systems. The results showed that solar panels equipped with a cooling system improved the operating efficiency compared to those without cooling. Among the tested methods, solar panels equipped with a heatsink and fan demonstrated the highest average operational efficiency, reaching 17.912%, followed by the water-cooling system, which achieved 17.832%. In contrast, solar panels without a cooling system showed the lowest average efficiency of 17.161%, highlighting the important role of thermal management in panel performance. However, when considering net energy output, the water-cooling system produced the highest net energy production, which was approximately 518.501 Wh, representing a 2.887% increase compared to the uncooled panel (503.951 Wh). In contrast, although the heatsink system improved instantaneous efficiency, its higher energy consumption resulted in a net energy output of only 455.900 Wh, which is 9.535% lower than that of the uncooled panel. These findings suggest that while active cooling improves solar panel performance, the choice of cooling method must consider both efficiency and energy consumption improvements to maximize net energy production.